EKUIVALENSI KESEPADANAN DENDA ATAS KERUSAKAN EKOLOGIS: ANALISIS QIRAAT Q.S AL-MAIDAH AYAT 95 - Maudy Muzalifah Azzahra; Siti Faridah; Tanfiu Billatifa; Najib Irsyadi (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This research examines the variations in qirā’āt (canonical recitations) of Surah Al-Mā’idah verse 95, focusing on the phrase fajazā’un mithlu mā qatala mina al-an‘ām and its implications for meaning construction and legal interpretation. The diversity of qirā’āt in this verse presents not only phonological differences but also variations in syntactic and semantic structures, particularly regarding the position of the word mithl, which can be interpreted as an adjective (na‘at), a genitive construction (iḍāfah), or a direct object (maf‘ūl bih). These distinctions influence the understanding of the concept of mithliyyah (resemblance) in determining kaffārah (expiation) for violations of iḥrām. Using a qualitative approach based on library research, this study analyzes qirā’āt data from classical tafsīr and qirā’āt texts, correlating them with legal constructions across various schools of Islamic jurisprudence (madhāhib). The findings indicate that each qirā’ah provides nuanced meanings: some emphasize general resemblance, others highlight more specific equivalence, and some underscore the implementational aspect of the penalty. These differences lead to two primary tendencies in jurisprudence: the approach of physical resemblance (al-mithliyyah al-ṣūriyyah) and the approach of value equivalence (al-qīmah). This study concludes that the diversity of qirā’āt does not alter the fundamental substance of the law but rather enriches the scope of ijtihād in determining fair forms of compensation.